Análisis de sistemas de transporte alternativas para la Vereda Yunguillo, Municipio de Mocoa-Putumayo. - Macías Jajoy, Carlos Parménides (Universidad Antonio Nariño, 2021)
This monograph describes the problems faced by indigenous reservations in Colombia due to the lack of infrastructure such as bridges, it is a means of transportation of vital importance for indigenous communities, mainly those that live in the Yunguillo reservation, which generates opportunities for the exploitation of agricultural products and livestock; For the development of this research, it will be proposed by comparing the construction processes and budget of the following means of transport, such as the pedestrian suspension bridge located over the Uchupayaco river, Champagnat village, Villagarzón municipality, Putumayo department and alternative transport by cable car, which is located on the Mocoa river, at the height of the San José del Pepino village, a well-known tourist route through the site called “End of the world” in the municipality of Mocoa; These structures used for transportation are built in the different villages of the Putumayo department. In order to assess the prefeasibility of the most suitable means of transport for rural areas. In order to present the different communication problems that occur in different indigenous communities and this affects the economic development of the population